Bruise Damage of Pomegranate during Long-term Cold Storage: Susceptibility to Bruising and Changes in Textural Properties of Fruit. (14th September 2020) - Hussein, Zaharan; Fawole, Olaniyi Amos; Opara, Umezuruike Obia
ABSTRACT: This study evaluated the bruise susceptibility of pomegranate fruit and textural properties of impact bruised fruit during long-term storage. Pomegranate fruit were stored at 5ºC and 85% relative humidity for 90 d. Impact tests were performed by dropping fruit from three drop heights (20, 40, and 60 cm) onto a flat hard surface to obtain different impact energy levels. The energy absorbed at impact, bruise volume (BV, mm3), bruise area (BA, mm2) and bruise susceptibility (BS, mm3/mJ) of pomegranate fruit were determined at 30 d interval for each impact dropped fruit. Textural properties for whole bruised and control (non-bruised) cold-stored fruit were carried out at 14 d intervals to determine the mechanical strength based on compression, cutting and puncture resistance tests. Based on impact tests, the increase in BV and BA of pomegranate fruit with increased drop heights and duration of cold storage were found significant ( p < .05) during the first 2 months of storage and then decreased in the last month of storage time. Pearson correlations indicated a strong linear relationship between the increase in both BV and BA with an increase in impact energy throughout the 90 d storage period. Fruit puncture resistance and whole fruit cutting force, cutting energy and power as well as fruit compression strength properties; firmness, and related textural properties increased with higher impact bruising and prolonged storage. The results obtained in this study demonstrate that long-term storage, indeed, influenced the susceptibility of pomegranate fruit to bruise, and altered fruit texture.